Reproductive history of Cynoglossus senegalensis (Kaup, 1858) from coastal waters of Greater Accra, Ghana - Amponsah, Samuel; Commey, Nii Amarquaye; Asiedu, Berchie; Failler, Pierre (Acta Aquatica: Aquatic Sciences Journal, 2023)
Some life history aspects including the reproductive characteristics and population dynamics of Senegalese tongue sole (Cynoglossus Senegalensis, Kaup, 1858), in the coastal waters of Ghana, were studied between August 2018 and July 2019. The length data of 606 specimens from the coastal waters of the Greater Accra region of Ghana was analyzed for size structure, growth pattern, condition factor, sex ratio and length at first maturity. The mean length varied significantly (p -value < 0 .001) with sex (31.3 ± 0.4 cm in males, 34.3 ± 0.4 cm in females). Condition factor (K) did not vary significantly (p -value = 0.054) with sex (i.e. 0.466 ± 0.002 in males, 0.476 ± 0.004 in females). The gonadosomatic index (GSI) varied significantly p -value < 0 .001) with sex (2.29 ± 0.30 in males), (3.94 ± 0.25 in females) and spawning peaks in April and July. Five maturity stages were recorded for both sexes with the size at first maturity for females and males estimated at 44.1 cm and 38.3 cm, respectively. In conclusion, the assessed fish species is likely to experience recruitment failure in the future, if appropriate management measures are not in place. Reduction in fishing efforts ad establishment of closed season is highly recommended.Keywords: Cynoglossus senegalensis; Ghana; Growth; Fisheries management; Life history.